Profil Pedagang Cengkeh di Kecamatan Busungbiu, Kabupaten Buleleng - JIWANTARI, KETUT MIA; ARTINI, NI WAYAN PUTU; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2022)
Profile of Clove Traders in Busungbiu Sub-District, Buleleng Regency Cloves are one of the potential plantation commodities to be cultivated in Buleleng because they have high economic value. Clove trading is a promising source of livelihood because market demand is quite high. This study aims to determine the profile of clove traders in Busungbiu District, Buleleng Regency and to determine the size of the profits from the clove trading business. Primary data were obtained through interviews with 50 clove traders and secondary data were obtained from books, previous research, and other sources on the internet. This research uses descriptive analysis. The results of the study provide an overview of the profiles of clove traders in Busungbiu District who are classified as new traders, with an average trading experience of 8.5 years. From July to September 2019, the average capital required to trade cloves is IDR 260,400,000.00. Most of the clove traders use their own capital with a sales volume of 18,302 kg of cloves. Within these months, clove traders get a profit of at least IDR 4,551,333.00 and a maximum of IDR 63,292,668.00 with an average profit of IDR 16,790,660.00 or IDR 5,968,866.00 per month. The average profit of bonded traders is greater because the cost of raw materials issued is smaller. But bonded traders must be proficient in interpreting prices in the bond system.